V, Efektivitas Efektivitas Sistem Temu Kembali OPAC Perpustakaan Universitas Bengkulu - SIDABUTAR, VERANITA; Gunaidi, Aang (UPT Perpustakaan Universitas Bengkulu, 2023)
An information retrieval system is a system capable of storing, searching, and maintaining various types of information in various formats. The function this information retrieval system is then applied to the existing retrieval services in library. This study aims to determine the effectiveness of network collaboration carried ot by the library as an optimization of teh information retrieval services provided. The research method uses a quaitative method with a descriptive approach, and the data collection method uses observation activities , interview, and informants who are IT staff of the Bengkulu University Library. Data analysis was carried out through data reduction, data renderig, and drawing conclusions. The results of teh study show that network collaboration with OPAC applications that are applied to information retrieval services is optimal and effective for librarians and users.